2007
DOI: 10.1093/jac/dkm273
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide resistance mechanisms among Streptococcus pneumoniae isolated over 6 years of Canadian Respiratory Organism Susceptibility Study (CROSS) (1998 2004)

Abstract: The prevalence of efflux-based macrolide resistance in S. pneumoniae in Canada remained steady between 1998 and 2004. Macrolide resistance due to erm(B) decreased over the same time period, with a rapid increase in isolates with both erm(B) and mef(A) macrolide resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
5
36
0
1
Order By: Relevance
“…More than 50% of the macrolide-resistant population were erm (B)+mef (A) positive (23). In Canada, erm (B) and mef (A) positive isolates represent 4% in 1998 and 12% in 2004 and one major cluster containing 36 (72%) of the 50 isolates was described (24).…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of the macrolide-resistant population were erm (B)+mef (A) positive (23). In Canada, erm (B) and mef (A) positive isolates represent 4% in 1998 and 12% in 2004 and one major cluster containing 36 (72%) of the 50 isolates was described (24).…”
Section: Discussionmentioning
confidence: 99%
“…DNA hybridization analysis of the 23S rRNA genes in S. criceti strains As mutations of the 23S rRNA genes and the rplD gene of S. pneumoniae are associated with resistance to macrolides (Tait-Kamradt et al, 2000;Wierzbowski et al, 2007), we first examined the 23S rRNA genes (rrl genes) of the four S. criceti strains by DNA hybridization. Genome sequence analysis of strain HS-6 T indicated that the genome contains five rrl genes and that five fragments, 12.8, 9.4, 9.2, 7.9 and 7.1 kb in size, should be detected after EcoRI digestion, whereas five fragments, 7.4, 6.0, 5.3, 3.8 and 3.3 kb in size, should be detected after EcoRI and BbsI double digestion (Richards Fig.…”
Section: Susceptibility Of S Criceti Strains To Antibioticsmentioning
confidence: 99%
“…Macrolide resistance in S. pneumoniae, a mitis group member, is mediated by the mef(A) gene encoding a macrolide efflux pump or by the erm(B) gene encoding a ribosomal RNA methylase (Wierzbowski et al, 2007), which methylates the N-6 position of nucleotide A2058, in Escherichia coli numbering, in 23S rRNA domain V Edited by Kazuhiro Kutsukake * Corresponding author. E-mail: htamura@iwate-med.ac.jp Note: Nucleotide sequence data reported are available in the DDBJ/EMBL/GenBank databases under the accession numbers AB981371−AB981373 and LC009004−LC009006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upper respiratory tract infections, injury, headache, back pain and hypoglycaemia are reported slightly more frequently than placebo in clinical trials 4 . To treat this upper respiratory tract infection, physicians usually prescribes macrolide like antibiotics 5 .…”
Section: Issn: 0975-8232mentioning
confidence: 99%